2018
DOI: 10.1186/s12864-018-5163-2
|View full text |Cite
|
Sign up to set email alerts
|

The genome of the water strider Gerris buenoi reveals expansions of gene repertoires associated with adaptations to life on the water

Abstract: BackgroundHaving conquered water surfaces worldwide, the semi-aquatic bugs occupy ponds, streams, lakes, mangroves, and even open oceans. The diversity of this group has inspired a range of scientific studies from ecology and evolution to developmental genetics and hydrodynamics of fluid locomotion. However, the lack of a representative water strider genome hinders our ability to more thoroughly investigate the molecular mechanisms underlying the processes of adaptation and diversification within this group.Re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 109 publications
1
62
0
Order By: Relevance
“…Torso-like has been duplicated several times within lineages of the Pancrustacea including in the Hemiptera, where there are apparent lineage-specific duplications of the gene in the pea aphid (Ac. pisum; Shigenobu et al, 2010;Bickel et al, 2013;Duncan et al, 2013), the kissing bug (R. prolixus; Mesquita et al, 2015) and the water strider (Gerris buenoi; Armisen et al, 2018). In this study, we have also identified a duplication of torso-like within the Lepidoptera, occurring prior to the diversification of moths and butterflies 250 Ma, with two copies of this gene maintained in the genomes of all sequenced lepidopteran species.…”
Section: Torso-likementioning
confidence: 55%
See 1 more Smart Citation
“…Torso-like has been duplicated several times within lineages of the Pancrustacea including in the Hemiptera, where there are apparent lineage-specific duplications of the gene in the pea aphid (Ac. pisum; Shigenobu et al, 2010;Bickel et al, 2013;Duncan et al, 2013), the kissing bug (R. prolixus; Mesquita et al, 2015) and the water strider (Gerris buenoi; Armisen et al, 2018). In this study, we have also identified a duplication of torso-like within the Lepidoptera, occurring prior to the diversification of moths and butterflies 250 Ma, with two copies of this gene maintained in the genomes of all sequenced lepidopteran species.…”
Section: Torso-likementioning
confidence: 55%
“…pisum; Shigenobu et al, 2010;Bickel et al, 2013;Duncan et al, 2013), the kissing bug (R. prolixus; Mesquita et al, 2015) and the water strider (Gerris buenoi; Armisen et al, 2018). Although it is possible that torso-like is older than this (indeed, we have only examined a single myriapod genome), it is not present in multiple chelicerate genomes, implying it did not evolve in the common ancestor of arthropods (Figs 4, S3, Data S5).…”
Section: Torso-likementioning
confidence: 99%
“…We combined these newly sequenced genomes with those of 48 previously sequenced arthropods creating a dataset comprising 76 species representing the four extant arthropod subphyla and spanning 21 taxonomic orders. Using the OrthoDB gene orthology database 7 , we annotated 38,195 protein ortholog groups (orthogroups/gene families) among all 76 species (Fig. 1).…”
Section: An Arthropod Evolution Resourcementioning
confidence: 99%
“…This phylogeny is mostly consistent with previous arthropod phylogenies [8][9][10] , with the exception being that we recover a monophyletic Crustacea, rather than the generally accepted paraphyletic nature of Crustacea in respect to Hexapoda, the difference likely due to our restricted taxon sampling (see Methods). We reconstructed the gene content and protein domain arrangements for all 38,195 orthogroups in each of the lineages for the 76 species in the arthropod phylogeny. This resource (available at https://i5k.gitlab.io/ArthroFam/ and Table S11) forms the basis for the analyses detailed below and is an unprecedented tool for identifying and tracking genomic changes over arthropod evolutionary history.…”
Section: An Arthropod Evolution Resourcementioning
confidence: 99%
See 1 more Smart Citation